2021
DOI: 10.2147/ijn.s290263
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antitumor Efficacy Mediated by Liposomal Co-Delivery of Polymeric Micelles of Vinorelbine and Cisplatin in Non-Small Cell Lung Cancer

Abstract: Purpose Non-small cell lung cancer (NSCLC) is an aggressive tumor with high mortality and poor prognosis. In this study, we designed a liposome encapsulating polymeric micelles (PMs) loaded with vinorelbine (NVB) and cis-diamminedichloroplatinum (II) (cisplatin or CDDP) for the treatment of NSCLC. Materials and Methods Sodium poly(α- l -glutamic acid)-graft-methoxy-polyethylene glycol (PLG-G-PEG 5K ) was used to prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…If some special processes are used to prepare nanoparticles, liposomes, microspheres, cyclodextrin inclusions, etc., the bioavailability of drugs may be improved, and the side effects would be reduced [ 351 ]. Researchers have developed a liposomal co-delivery of polymeric micelle followed by a combination of vinorelbine and cisplatin and found that this liposome has a synergistic antitumor effect and obvious efficacy in reducing tumor size [ 352 ]. In addition, evodiamine was combined with a wood oil emulsive nanosystem to improve the solubility of the drug and the sensitivity of cancer cells to evodiamine [ 353 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…If some special processes are used to prepare nanoparticles, liposomes, microspheres, cyclodextrin inclusions, etc., the bioavailability of drugs may be improved, and the side effects would be reduced [ 351 ]. Researchers have developed a liposomal co-delivery of polymeric micelle followed by a combination of vinorelbine and cisplatin and found that this liposome has a synergistic antitumor effect and obvious efficacy in reducing tumor size [ 352 ]. In addition, evodiamine was combined with a wood oil emulsive nanosystem to improve the solubility of the drug and the sensitivity of cancer cells to evodiamine [ 353 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The second is when the storage space of the tensor kernel reaches the specified warning value due to the increase of TT rank. The last one is in front of some operations that need to use orthogonal characteristics [30][31] .…”
Section: Figure 3 Schematic Diagram Of Tensor Chain Decomposition Of ...mentioning
confidence: 99%
“…Liposome encapsulating polymeric micelles loaded with vinorelbine and cis-diamminedichloroplatinum (II) (cisplatin) have also been designed for the treatment of non-small-cell lung cancer, an aggressive tumor with high mortality and poor prognosis [ 166 ]. The stability of this formulation has been tested in PBS (pH 7.4) solvent and 10% plasma, showing no significant change in particle size and a slight increase in the polydispersity index, indicating that the particles could accumulate if stored for more than 72 h, and, therefore, that the co-delivered drugs were protected from metabolism and rapid elimination.…”
Section: Anticancer Drugs In Nanoparticle Systemsmentioning
confidence: 99%